Unconventional Shrinkage of Hot Electron Distribution in Metal Directly Visualized by Ultrafast Imaging. Issue 2 (8th January 2023) - Gao, Guoquan; Jiang, Lan; Xue, Bofeng; Yang, Fei; Wang, Ti; Wan, Yan; Zhu, Tong
Abstract: Elucidation of hot carrier transport and cooling mechanisms at the micro‐/nanoscale is critical for optoelectronics, thermal management, and photocatalysis. Spatiotemporal evolution of hot electrons is usually convoluted with their ultrafast dynamics. Herein, an ultrafast microscopy is employed to directly track the spatiotemporal distribution of photoexcited hot electrons, providing a transformative approach to unravel the competitive relationship of transport and cooling. In the temporal evolution profiles of hot electron distribution, an anomalous contracting stage showing obvious thickness and fluence dependency is observed, with a characteristic end time indicating the completion of electron–phonon (e‐ph) thermalization. Hot electron transport plays a prominent role in the competition with e‐ph coupling, while interfacial heat dissipation dominates nonequilibrium state evolution with thickness below ballistic length. This work significantly enriches the tool kit of ultrafast techniques and provides guidance for rational design and optimization of micro‐/nanodevices. Abstract : Hot electron transport is usually convoluted with ultrafast cooling dynamics at the micro‐/nanoscale in metal‐based devices. By integrating high‐resolution microscopy with ultrafast spectroscopy, the spatiotemporal evolution of hot electron temperature is directly monitored. Anomalous contraction of metal hot electron distribution reflects the competition among hot electron transport, electron–phonon coupling, and interfacial heat dissipation.